Times of History: An Overview of Time Studies Related to the Theory of History (Concepts, Issues, and Trends) - Cardoso Jr, Hélio Rebello; Mudrovcic, María Inés; Landwehr, Achim (História (São Paulo, Brazil), 2023)
Abstract This article proposes a four-layered diagram that displays as an overview of the current field of historical time studies according to the following branches of investigation: 1) the metaphysics of natural time, 2) the metaphysics of historical time, 3) the regimes of historicity, and 4) historiographical regimes. By defining these fields and their connections, identifying essential concepts, revealing the questions they address, and sketching tendencies that have emerged since the 2000s, this article tackles historical temporality as a theoretical and historiographical subject. This framework, which portrays the state of the art in temporal studies, allows for the presentation and classification of the variety of contributions gathered in this special edition. Resumo Este artigo propõe um diagrama de quatro camadas que exibem os subcampos de investigação como uma visão geral do campo atual dos estudos do tempo histórico: 1) a metafísica do tempo natural, 2) a metafísica do tempo histórico, 3) os regimes de historicidade e 4) os regimes historiográficos. Ao definir esses campos e suas interrelações, apontar os principais conceitos, as questões que abordam e as tendências que se constituíram desde o início dos anos 2000, este artigo aborda a temporalidade histórica como tema teórico e historiográfico. Este quadro, que apresenta o estado da arte dos estudos temporais, permite apresentar e classificar a variedade de contribuições que esta edição especial reúne.